Analisis Survei Penerapan Olahraga Tradisonal Pada Guru Pendidikan Jasmani dan Olahraga Kesehatan Sekolah Menengah Kejuruan - Abdul Wahid Habibi; Ega Trisna Rahayu; Febi Kurniawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study was aimed at knowing the application of traditional sports to the practice of learning physical education in SMK Negeri 1 Rawamerta. The formulation of the case in this study is to determine the application of traditional sports in physical education learning practices in SMA Negeri in Rawamerta District. This research is a narrative and quantitative research. The method used is a survey. The research instrument used is a questionnaire. The sample in this study was a physical education teacher totaling 4 teachers. At a public vocational high school in the district of Rawamerta. The data analysis technique uses narrative analysis, which is expressed in percentage form. The results of the survey on the application of traditional sports to physical education learning practices in State Vocational Schools in Rawamerta District, which have been applied to 98% of Rawamerta Vocational Schools. Holistically, traditional sports have been applied in State Vocational Schools in Rawamerta District. For the results in this study, it was very successful in efforts to implement traditional sports carried out in various schools with a success rate of above 90%